2015
DOI: 10.1051/0004-6361/201527297
|View full text |Cite
|
Sign up to set email alerts
|

Age consistency between exoplanet hosts and field stars

Abstract: Context. Transiting planets around stars are discovered mostly through photometric surveys. Unlike radial velocity surveys, photometric surveys do not tend to target slow rotators, inactive or metal-rich stars. Nevertheless, we suspect that observational biases could also impact transiting-planet hosts. Aims. This paper aims to evaluate how selection effects reflect on the evolutionary stage of both a limited sample of transiting-planet host stars (TPH) and a wider sample of planet-hosting stars detected throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 37 publications
5
94
0
1
Order By: Relevance
“…A K dwarf like Kepler-444 A can nonetheless be more active than the Sun, and we used the study of the transiting super-Earth HD 97658 b made by Bourrier et al (2016a) to estimate the variability of its K1-type host star at Ly-α. HD 97658 could be as old as Kepler-444 (9.7±2.8 Gyr;Bonfanti et al 2016), and was observed at three epochs in the Ly-α line. The peaks of the line revealed systematic variations, attributed to an active upper chromosphere/corona, which reach a maximum of ∼15% from one HST orbit to another.…”
Section: Stellar Variabilitymentioning
confidence: 98%
“…A K dwarf like Kepler-444 A can nonetheless be more active than the Sun, and we used the study of the transiting super-Earth HD 97658 b made by Bourrier et al (2016a) to estimate the variability of its K1-type host star at Ly-α. HD 97658 could be as old as Kepler-444 (9.7±2.8 Gyr;Bonfanti et al 2016), and was observed at three epochs in the Ly-α line. The peaks of the line revealed systematic variations, attributed to an active upper chromosphere/corona, which reach a maximum of ∼15% from one HST orbit to another.…”
Section: Stellar Variabilitymentioning
confidence: 98%
“…In addition, Denissenkov (2010) shows that stellar rotational speeds converge towards similar values after a few billion years, regardless of their initial spin rate; consistently Meibom et al (2015) confirm a well-defined periodage relation up to ∼ 2.5 Gyr. Taking all these considerations into account, Bonfanti et al (2016) explain how we use the gyrochronological relation by Barnes (2010) and the log R HK -age relation by Mamajek & Hillenbrand (2008) to compute conservative age lower limits, which they denote by τ v and τ HK , respectively. Just in assessing age lower limits, the code already takes care of the above-mentioned caveats such that the user is not obliged to be aware of them, and we attain the goal of possible discarding of unlikely pre-MS isochrones before interpolation.…”
Section: Possible Removing Of Isochrone Degeneraciesmentioning
confidence: 99%
“…Just in assessing age lower limits, the code already takes care of the above-mentioned caveats such that the user is not obliged to be aware of them, and we attain the goal of possible discarding of unlikely pre-MS isochrones before interpolation. Bonfanti et al (2016) also note that the parameter degeneracies on the HRD under the turn-off (TO) can be broken by using ρ . The mean stellar density is higher in the MS phase than in the pre-MS, thus it enables us to distinguish MS stars from pre-MS stars and to set a conservative age lower limit called τ ρ .…”
Section: Possible Removing Of Isochrone Degeneraciesmentioning
confidence: 99%
“…To achieve the second goal, we considered the CHEOPS sample specified in Table 6. The estimate of stellar output parameters has been done thanks to the Isochrone Placement algorithm described in Bonfanti et al (2015Bonfanti et al ( , 2016. Interpolation in theoretical grids of tracks and isochrones have been made considering PARSEC 2 evolutionary models, version 1.2S (see Bressan et al 2012;Chen et al 2014;and references therein).…”
Section: Expected Stellar Uncertaintiesmentioning
confidence: 99%